Qualitätsmanagement bei der Telefonreanimation - mehr Daten für mehr Überlebende: Konsentierung eines Zusatzmoduls zum Deutschen Reanimationsregister = Quality management in telephone resuscitation - more data for more survivors : consensus for an additional module for the German Reanimationsregister - Marung, Hartwig; Weiß, Christel (Notfall & Rettungsmedizin, 2015)
Background: The success of out-of-hospital resuscitation is based primarily on the rapid initiation of action by first responders. A concept for increasing the percentage of first responders is the guidance of the caller by a dispatcher control center, so-called telephone resuscitation (T-CPR). The widespread introduction of T-CPR is one of the core requirements of the 2010 ILCOR guidelines. The aim of the process described below was to create the basis for structured quality management in T-CPR by identification of quality indicators. Material and methods: A four-stage Delphi procedure, in which six experts took part in rescue coordination centers in the field of health services research, was used for validation. During each of the first three stages, 12 of twelve 53 variables, and in the fourth stage 10 of 38 variables were selected. The process was controlled by the corresponding authors via e-mail. Results: The consensus among the ten variables (e.g., patient age, length of the call, reasons for hindrance in T-CPR, use of written instructions, instructions for ventilation) achieved an agreement of 0.941, whereby a value of 1.0 indicates complete agreement. Discussion: The Delphi process showed high agreement between the experts. The implementation of the data set will allow conclusions to be made about which factors are essential for success in T-CPR. On this basis, the concept can be further developed with the goal of saving more lives.